REKONSTRUKSI KEBIJAKAN PENDIDIKAN BERPERSPEKTIF GENDER DI KABUPATEN BANYUMAS - Ahmad Luthfi Hamidi; Durrotun Nafisah; Aris Nurrohman (IAIN Purwokerto, 2020)
The quality of public policy in educational field seen from gender perspective can be divided into three levels: responsive, neutral, and potentially bias to gender issues. Among the policies of education in Banyumas Regency, which is stated in Strategic Planning (Renstra) of 2008-2013 and Renja of 2012, there was only one policy which could be categorized into responsive to gender issues, while others were neutral to gender issues. From this fact, it can be concluded that gender has not been a mainstream in Education Affairs Office (Dinas Pendidikan) of Banyumas Regency. The activities concerning gender issues have been just programmed and only incidentally realized by one section of the office. The success or failure of the integration of gender in educational policy in Banyumas regency is influenced by four factors of its formulation, namely the capacity of human resources, capacity building, the strength of networking, and organization culture.